Adiposity and breast, endometrial, and colorectal cancer risk in postmenopausal women: Quantification of the mediating effects of leptin, C‐reactive protein, fasting insulin, and estradiol. (20th January 2022) - Dashti, S. Ghazaleh; Simpson, Julie A.; Viallon, Vivian; Karahalios, Amalia; Moreno‐Betancur, Margarita; Brasky, Theodore; Pan, Kathy; Rohan, Thomas E.; Shadyab, Aladdin H.; Thomson, Cynthia A.; Wild, Robert A.; Wassertheil‐Smoller, Sylvia; et al.
Abstract: Background: Mechanisms underlying the adiposity–cancer relationship are incompletely understood. We quantified the mediating roles of C‐reactive protein (CRP), leptin, fasting insulin, and estradiol in the effect of adiposity on estrogen receptor (ER)‐positive breast, endometrial, and colorectal cancer risk in postmenopausal women. Methods: We used a case–cohort study within the Women's Health Initiative Observational Study, analyzed as a cumulative sampling case–control study. The study included 188 breast cancer cases, 98 endometrial cancer cases, 193 colorectal cancer cases, and 285 controls. Interventional indirect and direct effects on the risk ratio (RR) scale were estimated using causal mediation analysis. Results: For breast cancer, the total effect RR for BMI ≥30 versus ≥18.5–<25 kg/m 2 was 1.87 (95%CI, 1.11–3.13). The indirect effect RRs were 1.38 (0.79–2.33) through leptin and CRP, 1.58 (1.17–2.43) through insulin, and 1.11 (0.98–1.30) through estradiol. The direct effect RR was 0.82 (0.39–1.68). For endometrial cancer, the total effect RR was 2.12 (1.12–4.00). The indirect effect RRs were 1.72 (0.85–3.98) through leptin and CRP, 1.42 (0.96–2.26) through insulin, and 1.24 (1.03–1.65) through estradiol. The direct effect RR was 0.70 (0.23–2.04). For colorectal cancer, the total effect RR was 1.70 (1.03–2.79). The indirect effect RRs were 1.04 (0.61–1.72) through leptin and CRP, 1.36 (1.00–1.88) through insulin, and 1.02 (0.88–1.17) through estradiol. The direct effect RR was 1.16 (0.58–2.43). Conclusion: Leptin, CRP, fasting insulin, and estradiol appear to mediate the effect of high BMI on cancer risk to different extents, with likely varying degrees of importance between cancers. These insights might be important in developing interventions to modify obesity‐associated cancer risk in postmenopausal women.